2016
DOI: 10.1007/s40279-016-0561-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Teacher Training in School-Based Physical Education Interventions to Improve Fundamental Movement Skills and/or Physical Activity: A Systematic Review

Abstract: It is clear that whilst teachers are capable of making substantial improvements in student outcomes in PA and FMS, the findings of this review suggest the teacher training component of school-based PA and/or FMS interventions is not only under-reported but is under-studied, and, perhaps as a result, the value of teacher training is not widely understood. What remains unclear, due to poor reporting, is what role teacher training is having on these outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(137 citation statements)
references
References 101 publications
(357 reference statements)
2
120
0
2
Order By: Relevance
“…For example, Jones et al [15] found small to medium effect sizes in favor of the FMS professional development intervention group compared to the control group. Despite the importance of FMS, the impact of FMS interventions on ECEC educators appears to be understudied [16]. It is therefore vital for studies to evaluate the impact of FMS professional development programs on educator physical activity practices.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jones et al [15] found small to medium effect sizes in favor of the FMS professional development intervention group compared to the control group. Despite the importance of FMS, the impact of FMS interventions on ECEC educators appears to be understudied [16]. It is therefore vital for studies to evaluate the impact of FMS professional development programs on educator physical activity practices.…”
Section: Introductionmentioning
confidence: 99%
“…In EQUIP schools, a possible explanation regarding why more significant changes were not observed may be that increasing the amount of equipment alone is not enough to increase PA . In fact, teachers may have a greater impact than equipment on the amount of PA that students participate in due to their instructions and encouragement . It is also possible that the type of equipment provided to the students was not conducive to increasing the PA for those students in particular, as not all types of equipment have been shown to be equally effective in increasing PA .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, his time (teacher overload) or availability, his training, having a supportive school environment, technical support, his skills proficiency as well as his own characteristics, level of commitment and motivation have been found as major elements to explain the successful implementation of intervention programs (Naylor et al 2015). Another review focused on the characteristics of teachers training in schoolbased education interventions to improve fundamental movement skills and physical activity practice (PAP) (Lander et al 2017). The authors from this review found that teachers training that provide pedagogy content, theoretical models or frameworks, follow-ups and technical support to the teacher during the intervention programs, were the most effective factors at improving the students PAP (Lander et al 2017).…”
Section: Factors That Influence Intervention Strategies Implementationmentioning
confidence: 99%